Effect of Different Vitamin D Levels on Cognitive Function in Aged Mice After Sevoflurane Anesthesia - Zhang, Jialei; Zhang, Xiaoling; Yang, Yongyan; Zhao, Jun; Hu, Wenqing; Yu, Yonghao (Frontiers in Aging Neuroscience, 2022)
Abstract Although the biological relationship between vitamin D deficiency and cognitive function has been recognized by many scholars, the theoretical mechanisms involved are still not well understood. In this study, we demonstrated the role of vitamin D in alleviating the cognitive dysfunction in aged mice caused by sevoflurane anesthesia. Forty female C57BL/6 mice aged 12 months were selected for the experiment. VD (-) and VD (+) mouse models and sevoflurane anesthesia models were established. Mice were randomly divided into normal elderly group (NC group), normal aged mice + sevoflurane anesthesia treatment group(NS group), aged VD(-) mice + sevoflurane anesthesia treatment group(VD(-) group), and aged VD (+)+sevoflurane anesthesia treatment group(VD(+) group). To compare the emergence time after sevoflurane anesthesia in aged mice with different levels of vitamin D and to test the cognitive function of four groups through the water maze. Inflammatory factor expression and cholinergic activity in hippocampal tissue of all mice were measured at the end of behavioral tests. These data show that, low levels of vitamin D aggravated the delayed emergence and cognitive dysfunction in aged mice caused by sevoflurane anesthesia, while higher levels of vitamin D mitigated this impairment by reducing inflammatory factor expression and enhancing cholinergic activity in the hippocampus.